Kualitas Pelayanan Publik Pemerintah Daerah (Studi Persepsional Terhadap Pelayanan UPTSA Kabupaten Bantul ) - MUCHAMAD ZAENURI (Jurnal Ilmu Pemerintahan, 2009)
In the current era of regional autonomy, the local governments are also req uired to be able to apply the paradigm of good governance in every aspect of governance. Implementation of good governance, in local government, in the implementation of activities related to UPTSA community service products, including in Bantul Yogyakarta Province requires a synergistic interaction between the three components of government, society and industrialist. The bad performance of public services, among others not yet implemented due to transparency and accountability in the administration of public services. Therefore, public services must be implemented in a transparent and accountable by each unit of government service because the quality of the performance of public service bureaucracy has broad implications in achieving the public welfare.